Correlational Analysis of Physiological and Psychological Factors with Fatigue on Chronic Kidney Disease Patients Undergoing Hemodialysis - Prastiwi, Firman; Wihastuti, Titin Andri; Ismail, Dina Dewi Sartika Lestari (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Fatigue is a major problem commonly experienced by chronic kidney disease patients undergoing hemodialysis. However, currently, the factors that correlate with fatigue in chronic kidney diseases patients undergoing hemodialysis are not comprehensive studies and there are still contradictory results from previous studies in Indonesia. This study aims to investigate the correlational analysis of physiological and psychological factors with fatigue on chronic kidney disease patients undergoing hemodialysis. This studi use a cross-sectional study with a sample count of 80 patients undergoing hemodialysis in Yarsi Public Hospital Pontianak, Indonesia. The sampling was carried out using the total sampling approach. A FACIT fatigue scale tool and depression and anxiety stress scale (DASS) 42 were employed to measure fatigue and depression, while hemoglobin and urea levels were taken based on medical history. The Spearman’s Rho test shows the physiological factor from the urea level had an insignificant correlation with fatigue (p-value 0.585). The physiological factor of hemoglobin level had a weak positive correlation (p-value 0.001 and r= 0.349) with fatigue. The psychological factor of depression had a strong negative correlation (p-value 0.000 and r = -0.812) with fatigue. The psychological factor of depression was the dominant factor causing fatigue than other factors based on the standardized coefficient beta value of -0.717. Factors that correlate with fatigue on chronic kidney disease patients undergoing hemodialysis are hemoglobin levels and depression. The most dominant factor influencing fatigue in chronic kidney disease patients undergoing hemodialysis is depression.Abstrak: Kelelahan merupakan masalah utama yang sering dialami oleh pasien gagal ginjal kronik yang menjalani hemodialisis. Namun, saat ini faktor-faktor yang berkorelasi dengan kelelahan pada pasien gagal ginjal kronik yang menjalani hemodialisis belum diteliti secara komprehensif dan masih terdapat hasil yang kontradiktif dengan penelitian-penelitian sebelumnya di Indonesia. Penelitian ini bertujuan untuk mengetahui analisis korelasi faktor fisiologis dan psikologis dengan kelelahan pada pasien gagal ginjal kronis yang menjalani hemodialisis. Penelitian ini menggunakan studi potong lintang dengan jumlah sampel 80 pasien yang menjalani hemodialisis di RSU Yarsi Pontianak, Indonesia. Pengambilan sampel dilakukan dengan menggunakan pendekatan total sampling. Alat FACIT Fatigue Scale dan depression and anxiety stress scale (DASS) 42 digunakan untuk mengukur kelelahan dan depresi, sementara kadar hemoglobin dan urea diambil berdasarkan riwayat medis. Uji Spearman's Rho menunjukkan faktor fisiologis dari kadar urea tidak terdapat korelasi dengan kelelahan (p-value 0,585). Faktor fisiologis kadar hemoglobin memiliki korelasi positif yang lemah (p value 0,001 dan r= 0,349) dengan kelelahan. Faktor psikologis depresi memiliki korelasi negatif yang kuat (p-value 0,000 dan r = -0,812) dengan kelelahan. Faktor psikologis depresi merupakan faktor dominan penyebab kelelahan dibandingkan faktor lainnya berdasarkan nilai koefisien standar beta sebesar -0,717. Faktor yang berhubungan dengan kelelahan pada pasien penyakit ginjal kronik yang menjalani hemodialisis adalah kadar hemoglobin dan depresi. Faktor yang paling dominan mempengaruhi kelelahan pada pasien penyakit ginjal kronis yang menjalani hemodialisis adalah depresi.